Measuring the impacts of Bus Rapid Transit on residential property values: The Beijing case. (December 2016) - Deng, Taotao; Ma, Mulan; Nelson, John D.
Abstract: Bus Rapid Transit (BRT) has emerged as a cost-effective transport system for urban mobility. The study uses the hedonic price model to investigate the impacts of BRT on residential property values in Beijing, where BRT has been in service for over 6 years. The empirical analysis suggests that BRT has positive impacts on surrounding property values. The hedonic price model shows that for every 100-m closer to the BRT station, asking prices of residential properties increase by between 1.32% and 1.39%. The study suggests that accessibility improvement, rather than the type of transit system, has certain influence on property values. The paper underscores the importance of considering the application of value-capture tools to help finance BRT investments and calls for complementary investment policies to enhance property value impacts.